HEMI-MAXILLECTOMY RESTORED WITH HOLLOW BULB CAST PARTIAL OBTURATOR - Patil, Dr. Rahul (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Throughout recorded history, it is evident that man has found a need to attempt to restore or replace the eyes and facial parts of those who were either unfortunate enough to have congenital deformities, or to have suffered from trauma or disease. The definition is quite broad. It could include such important dental specialties as fixed and removable prosthodontics, since these specialties also deal with replacing missing tissues. Yet, the term is used to imply only those intraoral, para oral or extraoral areas that are not within the scope of these other dental specialties. Many phases of maxillofacial prosthetics are merely logical extensions of prosthodontics to those areas that are part of them. The basic material and techniques used in both fields are also similar. The success, like in prosthodontics depends on full cognizance of the principles that underlie facial harmony, color matching, anchorage and retention, weight bearing and leverage, durability and strength of materials used, tissue compressibility and tissue tolerance.